Therapy with CD4+CD25+ T regulatory cells – should we be afraid of cancer? - Gliwiński, Mateusz; Piotrowska, Magdalena; Iwaszkiewicz-Grześ, Dorota; Urban-Wójciuk, Zuzanna; Trzonkowski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2019)
This review focuses on the role of regulatory T cells (Tregs) in the process of carcinogenesis. The controversy of this issue arose due to the increasing therapeutic use of Tregs in humans (inter alia, in the treatment of autoimmune diseases). It is mainly due to potential dangers related to immunosuppressive activity of these cells, especially regarding cancer. The natural function of regulatory T cells (which is the suppression of excessive activity of the immune system) is purportedly linked to an increased risk of cancer initiation. This work brings together and summarizes the most important reports of researchers dealing with this problem and attempts to explain doubts and fears related to Tregs and their uncertain connection with cancer initiation and progression. It is clearly shown that regulatory T cells are associated with acceleration of existing tumors (they are attracted by microenvironments created by cancer cells) but cannot initiate them on their own.